FAMILY SIZE, INCREASING BLOCK TARIFF AND ECONOMIES OF SCALE OF HOUSEHOLD ELECTRICITY CONSUMPTION IN VIETNAM FROM 2010 TO 2014 - Nguyen, Hoai Son; Minh, Ha Duong (Journal of International Economics and Management, 2018)
Household electricity consumption potentially offers economies of scale, since lighting, cooling or cooking can be shared among household members. This idea needs to be tested empirically. Under an increasing block tariff schedule the marginal and average price of electricity increases with total consumption. Does this effect offset economies of scale in the larger families? This paper uses data from Vietnam Household Living Standard Survey (VHLSS) in 2010, 2012 and 2014 to investigate whether there are economies of scale for Vietnam household electricity consumption in that period. The data will be tested formally by an OLS model and checked robustness by visualization of local linear regressions. Estimated results and robustness check confirm that in general, economies of scale do exist for household electricity consumption in Vietnam from 2010-2014.